Effect of acupuncture therapy for postoperative gastrointestinal dysfunction in gastric and colorectal cancers: an umbrella review - Wang, Yuhan; Wang, Linjia; Ni, Xixiu; Jiang, Minjiao; Zhao, Ling (Frontiers in Oncology, 2024)
Background Gastrointestinal dysfunction is a prevalent postoperative complication in patients undergoing surgery for gastric cancer and colorectal cancer. Acupuncture holds promise as a great potential therapeutic intervention. The efficacy of acupuncture therapy for postoperative gastrointestinal dysfunction has been assessed in some studies, however, the variability in results and study quality influences practical clinical application. Therefore, it is necessary to summarize and analyze the published clinical research data in this field. Objective This study aimed to synthesize evidence from systematic reviews and meta-analyses in order to assess the efficacy of acupuncture therapy for postoperative gastrointestinal dysfunction in patients with gastric and colorectal cancer. Design Umbrella review of systematic reviews and meta-analyses. Methods We searched China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform (Wanfang), China Science and Technology Journal Database (VIP), Chinese biomedical literature service system (SinoMed), PubMed, Embase, Cochrane Library, and Web of Science for all systematic review/meta-analysis of acupuncture for postoperative gastrointestinal dysfunction in gastric and colorectal cancers. From the establishment of the database to July 8, 2023. Two independent reviewers conducted literature extraction and evaluation. The quality of included studies was assessed using The preferred reporting items for systematic reviews and meta-analysis statements 2020 (PRISMA2020), the quality of the methods was assessed using a measuring tool to assess systematic reviews 2 (AMSTAR 2), and the level of evidence was assessed using the grading of recommendations assessment, development, and evaluation (GRADE). The statistical analysis was conducted using RevMan 5.4, and the effect size was expressed as Odds Ratio (OR), Mean Difference (MD), and 95% confidence interval (CI) based on the extracted data type (test level α= 0.05). The heterogeneity was assessed using the I2 statistic and Q-test (χ2). The outcome indicators such as time to first defecation and time to first flatus were utilized as endpoints to assess the efficacy of different acupuncture therapies. Results A total of six systematic reviews/meta-analyses were included in this study, involving 12 different acupuncture therapies. PRISMA 2020 indicated that the studies all scored between 13-20.5. There were deficiencies in protocol and registration, assessment of the quality of evidence for outcome indicators, risk of bias, and declaration of conflict of interest. The AMSTAR 2 evaluations showed that five studies were very low quality and one was low quality. The level of evidence for various acupuncture interventions varied from very low to moderate. For patients with gastrointestinal dysfunction after gastric cancer surgery, ear acupressure [MD=-11.92, 95% (-14.39,-9.44), P<0.00001], moxibustion [MD=-19.16, 95% (-23.00,-16.22), P<0.00001], warm needling [MD=-12.81, 95% (-17.61,-8.01), P<0.00001], acupoint application [MD=-6.40, 95% (-10.26,-2.54), P=0.001], manual acupuncture [MD=-18.32, 95% (-26.31,-10.39), P<0.00001] and transcutaneous electrical acupoint stimulation (TEAS) [MD=-5.17, 95% (-9.59,-0.74), P=0.02] could promote the recovery of gastrointestinal function after surgery. For postoperative colorectal cancer patients, electroacupuncture [MD=-15.17, 95% (-28.81,-1.54), P<0.05], manual acupuncture [MD=-20.51, 95% (-39.19,-1.84), P<0.05], warm needling [MD=-18.55, 95% (-23.86,-13.24), P<0.05], ear acupressure [MD=-5.38, 95% (-9.80,-0.97), P<0.05], acupoint application [MD=-26.30, 95% (-32.81,-19.79), P<0.05], ear acupressure+acupressure [MD=-9.67, 95% (-13.58,-5.76), P<0.05], ear acupressure+manual acupuncture [MD=-18.70, 95% (-21.01,-16.39), P<0.05], ear acupressure+moxibustion [MD=-22.90, 95% (-30.10,-15.70), P<0.05], moxibustion+acupressure [MD=-14.77, 95% (-20.59,-8.95), P<0.05] improved postoperative gastrointestinal function. In addition, the efficacy of acupressure [MD=-12.00, 95% (-31.60,7.60), P>0.05] needed to be further demonstrated. Conclusion Acupuncture therapy has a positive therapeutic impact on postoperative gastrointestinal dysfunction in gastric and colorectal cancers, but this finding should still be taken with caution.